The Perception of Communication on COVID-19 by Young Algerians - Elkaina Hammache (Health Economics and Management Review)
The aim of this article is to explore the meanings attributed by young people to their actions, ideas, and perceptions regarding the advent of COVID-19 and communication actions provided by the state. Generally speaking, any health crisis is accompanied by an information crisis, and the consequence of not controlling information is not controlling the crisis. In fact, uncontrolled information or absence of information increases the crisis amplitude, whereas appropriate communication can attenuate it. Communication covers all relationships, messages, and techniques used by a player to address different audiences with a view to supporting its actions, i.e., preparing them, explaining them, reinforcing their effectiveness, and evaluating them. Public communication is also considered to be formal, and is aimed at exchanging and sharing information of public interest, as well as maintaining social ties. The fight against the COVID-19 pandemic highlighted the challenges and difficulties of government communication in times of crisis. Therefore, the authors opted for the focus group technique with young people aged between 13 and 18. In line with a reasoned and sociologically-motivated selection of focus group participants, the latter had the advantage of gathering information of a qualitative type, “representative” of the context of interaction between individuals in which opinions and values evolve. Viewpoints, opinions, and representations were thus the product of interaction. This survey enabled us to discover that, contrary to the state’s strategy of using TV and radio to communicate about COVID-19, young people were not consumers of these media, and most of those interviewed claimed to be sufficiently informed but through social networks. This situation made young people more victims of “infodemia”, which was, however, a source of anxiety, fear, and stress. To channel and control their anguish, these young people turned to religion as a solution, and relaxation in the maintenance of confinement was clearly observed. This survey will enable public authorities to readjust their communication strategy towards young people.